O rzekomym kontratypie karcenia w celach wychowawczych - Piątkowska, Katarzyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
This article is dedicated to issues connected with non-statutory circumstances excluding unlawfulness of the prohibited act of so-called physical punishment for educational purposes, functioning under penal law. The author points out the conditions for the applicability of this exclusion, which have been brought about by the legal doctrine and judicial decisions, including those historical. The relationship between the scope of these excluding circumstances and Article 961 of the Family and Guardianship Code introduced in 2010, prohibiting the use of corporal punishment, has also been examined. Likewise discussed are the procedural issues connected with the occurrence of non-statutory circumstances excluding unlawfulness of the prohibited act, and the possibility of employing the clause on insignificant social harm or necessity in certain cases traditionally included under physical punishment for educational purposes. The article concludes with reflections on the future of the circumstances excluding unlawfulness of the prohibited act in view not only of legislative changes, but also in terms of public awareness
Keywords: pozaustawowy kontratyp; karcenie w celach wychowawczych; wychowanie; kary cielesne